2012
DOI: 10.1007/s10067-011-1919-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory arthritis: case review and primary care perspectives

Abstract: Inflammatory arthritis (IA) has significant physical, psychosocial and economic consequences. Delays in diagnosis and initiation of treatment significantly impact on prognosis. The infrequent, variable, non-specific and, sometimes, indolent presentation make recognition of IA by primary care physicians (PCPs) challenging. To undertake an in-depth case review assessing the diagnostic trajectory of patients diagnosed with IA to inform development of practical recommendations to facilitate timely recognition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“… 5 Additionally, patients with negative rheumatoid factor are referred less frequently (66% vs 35%) 40 and had a longer period of delay (67 vs 22 days), 41 compared with those with positive rheumatoid factor. The same conclusion was reached by Kumar et al 11 This scenario is more dramatic when considering X-rays, 42 given the absence of radiographic changes in the early stage of the disease.…”
Section: Barriers At Each Levelsupporting
confidence: 57%
“… 5 Additionally, patients with negative rheumatoid factor are referred less frequently (66% vs 35%) 40 and had a longer period of delay (67 vs 22 days), 41 compared with those with positive rheumatoid factor. The same conclusion was reached by Kumar et al 11 This scenario is more dramatic when considering X-rays, 42 given the absence of radiographic changes in the early stage of the disease.…”
Section: Barriers At Each Levelsupporting
confidence: 57%
“…Variations in national health-care structures mean that factors contributing to referral delays need to be considered on a country-specific basis. Data on factors associated with GP referral delays of suspected RA in England are limited, but existing studies suggest that referral decisions are strongly influenced by test results (chiefly RF and radiographs), with negative/normal tests making referral less likely or timely [8–10]. These studies are limited by their regional nature [10], small size [8] or focus on a single factor [9].…”
Section: Introductionmentioning
confidence: 99%
“…A case-review analysis reported a median delay of 161 days, and a median of 5 visits, for specialist referral of RA patients after primary care presentation [ 30 ]. During the early stages of presentation, 82% of RA patients were not considered by their PCP to have an inflammatory pathology.…”
Section: Discussionmentioning
confidence: 99%